Sleep and salivary cortisol in preterm neonates: a clinical, randomized, controlled, crossover study - Fabrícia Magalhães Araújo; Mavilde da Luz Gonçalves Pedreira; Ariane Ferreira Machado Avelar; Márcia Lurdes de Cácia Pradella-Hallinan; Miriam Harumi Tsunemi; Eliana Moreira Pinheiro
ABSTRACT Objective: Analyze the influence of ear protectors on the baseline levels of salivary cortisol and response and total sleep time of preterm neonates during two periods of environmental management of a neonatal intermediate care unit. Method: A clinical, randomized, controlled and crossover study conducted with 12 preterm neonates. The use of ear protectors was randomized in two periods. Sleep evaluation was performed using one Alice 5 Polysomnography System and unstructured observation. Results: No significant difference was observed between the baseline levels of salivary cortisol and response in preterm neonates from the control and experimental groups, and no statistical significance was observed between the total sleep time of both groups. No relationship was observed between the baseline levels of cortisol and response and total sleep time. Conclusion: Ear protectors in preterm neonates did not influence the salivary cortisol level and total sleep time in the studied periods.